2018
DOI: 10.3389/fphys.2018.00448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Sensory Inputs to the Medial Giant Interneurons of Crayfish

Abstract: Crayfish are capable of two rapid, escape reflexes that are mediated by two pairs of giant interneurons, the lateral giants (LG) and the medial giants (MG), which respond to threats presented to the abdomen or head and thorax, respectively. The LG has been the focus of study for many decades and the role of GABAergic inhibition on the escape circuit is well-described. More recently, we demonstrated that the LG circuit is sensitive to the acute effects of ethanol and this sensitivity is likely mediated by inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(121 reference statements)
1
3
0
Order By: Relevance
“…Mellon and Christison-Lagay (2008) demonstrated that electrical stimulation of the bases of the antennules (i.e., antenna I) evoked action potentials in crayfish MG neurons, and the authors suggested that these inputs are mediated by mechanosensory hairs located on the flagella of the antennules. Similar results have been obtained after electrical stimulation of the antenna II nerve, which strongly depolarized the MG neurons and occasionally caused action potentials (Liu and Herberholz 2010;Swierzbinski and Herberholz 2018).…”
Section: The Mg Circuitsupporting
confidence: 85%
See 1 more Smart Citation
“…Mellon and Christison-Lagay (2008) demonstrated that electrical stimulation of the bases of the antennules (i.e., antenna I) evoked action potentials in crayfish MG neurons, and the authors suggested that these inputs are mediated by mechanosensory hairs located on the flagella of the antennules. Similar results have been obtained after electrical stimulation of the antenna II nerve, which strongly depolarized the MG neurons and occasionally caused action potentials (Liu and Herberholz 2010;Swierzbinski and Herberholz 2018).…”
Section: The Mg Circuitsupporting
confidence: 85%
“…Soon after, Swierzbinski and Herberholz (2018) showed that EtOH also facilitated the response of the MG neurons to sensory inputs. In addition, the authors highlighted the role of the GABAergic system in mediating this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Crayfish species are widely distributed, worldwide, in natural environments (https://en.wikipedia.org/wiki/Crayfish). Subjects for use in laboratory experiments can be purchased from pet stores (as we did for some of our subjects), biological suppliers (Swierzbinski & Herberholz, 2018; Teshiba et al, 2001), or are easily fished from the wild, if locally available (Datta et al, 2018; Imeh‐Nathaniel et al, 2017). This invertebrate species can be used for research within institutions that do not maintain regulatory approvals and facilities appropriate for vertebrate animal research subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Crayfish species are widely distributed, worldwide, in natural environments (https://en.wikipedia.org/wiki/Crayfish). Subjects for use in laboratory experiments can be purchased from pet stores (as we did for some of our subjects), biological suppliers (Swierzbinski and Herberholz, 2018; Teshiba et al, 2001), or are easily fished from the wild, if locally available (Datta et al, 2018; Imeh-Nathaniel et al, 2017). This invertebrate species can be used for research within institutions that do not maintain regulatory approvals and facilities appropriate for vertebrate animal research subjects.…”
Section: Discussionmentioning
confidence: 99%